The work of the African Union Liaison Office in building peace on the ground: A case study of Madagascar. Issue 1 (2nd January 2018) - Butedi, Nzolani François
ABSTRACT: Field offices are an increasingly important reality in the architecture of African peacemaking. Yet despite their importance in practice, in academic debates on peacebuilding and mediation, little attention has so far been paid to their work. This paper analyses the role of the African Union Liaison Office in the international efforts to re-establish constitutional order after the 2009 political crisis in Madagascar. The paper scrutinises the mandate, set-up and institutional capacities of the liaison office and reconstructs how and to what extent it has contributed to peacemaking and conflict prevention in Madagascar. It thereby particularly highlights the often ad hoc way the liaison office reacted to unprecedented and rapidly changing events on the ground and stresses the important role played by individual staff members in translating the liaison office's mandate into practice.